Strengthening the National Defense Education Curriculum from an Early Age - Teguh Soedarto; Hamidah Hendrarini; Teddy Prima Anggriawan; Anajeng Esri Edhi Mahanani; Zuhda Mila Fitriana (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2021)
State defense education ivfor PAUD children is very good. For example, in America in the era of President Obama, how to foster nationalism in future generations by visiting and inviting kindergarten children to camp at the White House. State defense education has also been carried out in many other countries in the world, one of which is Singapore. In Singapore there is a military museum, this discovery center is my inspiration. The method used is to analyze a problem by comparing the rules of other countries. If these threats cannot be anticipated as early as possible, it will have an impact on the fading of nationalism and the weakening of the nation's ideology due to the influence of other countries' ideologies that are not in accordance with the values ​​of Pancasila which can affect the weakness of the national defense system so that it can be penetrated by other countries that have interests. to divide the Indonesian nation.